(untitled) - Fabirkiewicz, Ann M. (New Jersey, 2016)
This book presents key aspects of organic synthesis – stereochemistry, functional group transformations, bond formation, synthesis planning, mechanisms, and spectroscopy – and a guide to literature searching in a reader-friendly manner.
Keywords: Chemistry, Organic,Hóa học hữu cơ; Textbooks,Sách giáo khoa